2010
DOI: 10.1074/jbc.r110.141408
|View full text |Cite
|
Sign up to set email alerts
|

Serpins Flex Their Muscle

Abstract: Inhibitory serpins are metastable proteins that undergo a substantial conformational rearrangement to covalently trap target peptidases. The serpin reactive center loop contributes a majority of the interactions that serpins make during the initial binding to target peptidases. However, structural studies on serpinpeptidase complexes reveal a broader set of contacts on the scaffold of inhibitory serpins that have substantial influence on guiding peptidase recognition. Structural and biophysical studies also re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(47 citation statements)
references
References 38 publications
2
45
0
Order By: Relevance
“…In the present Michaelis complex structure, we observed that PAI-1 RCL residues P4 -P5Ј directly contact the uPA catalytic site, accounting for about two-thirds of the total contact area. Such an interaction with a long extended PЈ region of serpin was also observed on the other Michaelis complexes paired with multispecific serpins (42), e.g. P4 -P6Ј in the antithrombin⅐S195A Factor Xa complex (14) and P4 -P5Ј in antithrombin⅐thrombin⅐heparin ternary complexes (43).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In the present Michaelis complex structure, we observed that PAI-1 RCL residues P4 -P5Ј directly contact the uPA catalytic site, accounting for about two-thirds of the total contact area. Such an interaction with a long extended PЈ region of serpin was also observed on the other Michaelis complexes paired with multispecific serpins (42), e.g. P4 -P6Ј in the antithrombin⅐S195A Factor Xa complex (14) and P4 -P5Ј in antithrombin⅐thrombin⅐heparin ternary complexes (43).…”
Section: Discussionmentioning
confidence: 81%
“…This long 37-loop permits uPA to be close to PAI-1 and to form a strong interaction that includes electrostatic and cation-bonds between the 37-loop and ␤-sheet B of PAI-1. Notably, the major involvement of PAI-1 ␤-sheet B in exosite interactions is also unique to the PAI-1⅐uPA complex: in most other serpin⅐protease Michaelis complexes, it is ␤-sheet C and the surrounding residues of serpin that mediate the interaction with the protease exosites (42). These structural features constitute the foundation of PAI-1 specificity for uPA.…”
Section: Discussionmentioning
confidence: 99%
“…These important interactions between the ␣ 2 -antiplasmin core domain, outside the immediate vicinity of P1-P1Ј, and the active site cleft of plasmin are also likely to contribute specificity to the serpin/protease interaction. Having additional exosite interactions is not uncommon in the serpin inhibition mechanism, as it may aid in the recognition of its target protein (18,19). Together with the specific binding of the ␣ 2 -antiplasmin C terminus to plasmin kringle domains, this leads to an exquisite specificity of the interaction minimizing off-target inhibition of non-cognate proteases.…”
Section: Discussionmentioning
confidence: 99%
“…The sequence of the RCL defines the enzyme specificity pattern of each serpin. All inhibitory serpins are irreversible covalent "suicide" protease inhibitors forming a highly stable covalent complex with their target enzyme, a complex detectable after gel electrophoresis in denaturing conditions [9,12,13]. A large set of information together with the serpin classification are also available at the following web site: http://en.wikipedia.org/wiki/Serpins.…”
Section: The Serpin Superfamilymentioning
confidence: 99%